Epidemiology and outcome of trauma victims admitted in trauma centers of tertiary care hospitals – A multicentric study in India - Kashid, Manoj (Int J Crit Illn Inj Sci, 2020)
BACKGROUND: Roadside trauma in India is an increasingly significant problem, particularly because of bad roads, irregular road signs, overcrowding, overspeeding, and bad traffic etiquettes. Adequate information on the characteristics of victims, causes of accidents, frequency, vehicles involved, alcohol intake, and outcome of management is essential for understanding and planning for better management. AIM: This study aimed to determine the characteristics of trauma (roadside accidents) victims admitted to various trauma centers in India. The purpose of this study is to examine the epidemiology of trauma within a local community in India through data gained from the different emergency centers and to analyze trauma patients to find the predictors that led to the deaths of trauma patients. MATERIALS AND METHODS: The present observational study involved trauma victims over 1-year period in three centers. Demographical details recorded were age, sex, alcohol intake, systolic blood pressure on arrival, respiratory rate, Glasgow Coma Scale (GCS) score, the interval between injury and admission, Injury Severity Score (ISS) risk factors, hospital stay, and outcome. RESULTS: A total of 2650 injuries were recorded in 2466 patients. The mean age was 42.45 ± 15.7 years, the mean ISS was 13.82 ± 6.2, and the mean GCS was 12.20 ± 4.1. The mean time to admission at different trauma centres was 48.41 ± 172.8 h. The head injury was the most common (29.52%). CONCLUSION: Road side accidents due to overspeeding was the most common cause whereas driving under the effect of alcohol was the second most common cause. Accidents are common because of bad traffic etiquette on Indian roads.